دراسة فعالية تقنية GuttaFlow2 في حشو النظام القنوي - سليم, باسم (Latakia University Journal -Medical Sciences Series, 2019)
Aim: To evaluate the efficacy of the GuttaFlow2 technique with or without the use of gutta-percha cone in the filling of root canal system. Methods: Twenty teeth with single root were chosen, and instrumented using hand files. Teeth were randomly divided into two experimental groups of 10 each, Group G1 (guttaflow2 with a cone), G2 (guttaflow2 without cone). All teeth were radiographed using a digital x-ray source and digital sensor, then examined by the (YES biotech) software. Results: guttaflow2 without cones was unable to fill all the working length of canals whereas all canals obturated with guttaflow2 with master cone were found filled to the working length, no significant statistical differences were found in the density of the two groups. Conclusion: The sealing ability of Guttaflow2 with master cone was morecomparable to the gold standard of obturation criteria more than guttaflow2 without master cone. الهدف: تقييم فعالية تقنيةGuttaFlow2 مع قمع كوتابيركا مع تقنية GuttaFlow2 دون قمع كوتابيركا في حشو الأقنية الجذرية. المواد والطرق: عينة من 20 سن بشري وحيد الجذر والقناة،تم تهيئتها وتحضيرها بالمبارد اليدوية، قسمت عشوائيا لعينتين n= 10 المجموعة (1): استخدمت تقنية GuttaFlow2 مع قمع كوتابيركا والمجموعة (2): استخدمت تقنية GuttaFlow2 بدون قمع كوتابيركا. صورت الأسنان باستخدام جهاز أشعة وحساس رقميين وتم تحليل الصور الشعاعية باستخدام برنامج (YES biotech). النتائج: وجد أن الفرق هام إحصائيا بين المجموعتين من حيث متغير طول حشوة القناة وملئها لكامل الطول العاملحيث وجد أنَّ تقنيةGuttaFlow2 مع قمع كوتابيركا أفضل من تقنية GuttaFlow2بدون قمع، في حين لم يكن الفرق هام إحصائيا بين المجموعتين من حيث متغير كثافة الحشوة الجذرية. الخلاصة: الحشو باستخدام تقنية GuttaFlow2 مع قمع كوتابيركا أفضل من تقنية GuttaFlow2 بدون قمع كوتابيركا.